SEWERS STINK! : HOW DOES WASTE GO DOWN? - Flynn, Riley; Butzer, Anna; Nuytten, Bobbie (North Mankato, Minnesota : CAPSTONE PRESS, 2018)
"Ever wonder how the sewer system works? Look no further! Discover the story behind the pipes beneath our feet. From facts on the first plumbing systems to information about how wastewater gets treated and cleaned. Readers will learn about why we need sanitation and the journey our waste and used water takes through the pipes"--Provided by publisher.
Includes index.
Bibliography : page 31
Keywords: Sewerage -- Juvenile literature; Sewage disposal -- Juvenile literature; Sewage disposal plants -- Juvenile literature; Sewage -- Purification -- Juvenile literature